Avaliação do processo logístico de recebimento/distribuição de materiais de consumo pelo Almoxarifado Central da Universidade Federal da Paraíba - Almeida, Jardel Beserra de (2022)
Currently, organizations are incessantly looking for new ways to become efficient and to offer quality products/services to consumers and users. In public organizations it is not different; however, successive budget cuts, social control and pressure to improve the quality of services have required from public managers a greater capacity to evaluate the performance of institutions and the processes involved in their functioning. In these circumstances, the present study aimed to evaluate and propose improvements in the Central Warehouse´s logistical operation of the Federal University of Paraíba (UFPB), the sector responsible for receiving, storing and distributing essential inputs to the functioning of this Higher Education Institution (HEI), based on the concepts and practices of lean methodologies: Kaizen and 5S, aiming to increase the productivity and efficiency of the referred sector. This research was structured on the deductive methods´s premises, it has an applied nature, with a qualitative approach of the problem, and a descriptive approach of the objectives. It was outlined as a logistics process´s case carried out in the sector, starting with a bibliographic survey on the main themes developed in the study, such as: public administration, evaluation in higher education, logistics, storage and warehouse, lean philosophy, kaizen and 5S methodologies, as well as an evidence collected analysis through a questionnaire and interviews applied in the sector´s employees. The research made it possible to carry out the main losses´ diagnosis or the Lean System´s waste, found in the warehouse, as well as identifying opportunities for improvement and proposing actions that may contribute to the identified losses´ elimination or reduction, as well as implementing and consolidating the culture of improvement. continuous activity in the sector and make the logistics process of the warehouse leaner, faster and more efficient, fulfilling the objective of receiving and distributing, as quickly as possible, the essential inputs for the proper functioning of UFPB, contributing for the institutional mission ´s achievement of this IFES.